Associations between dyadic language style matching and classroom observations of behaviorally inhibited children's sociability - Sem, Kathy; Shakiba, Nila; Rubin, Kenneth H.; Novick, Danielle R.; Druskin, Lindsay R.; Smith, Kelly; Danko, Christina M.; Chronis‐Tuscano, Andrea; Wagner, Nicholas J. (Social development (Oxford, England), 2025)
Children's sociability, the motivation and ability to initiate and maintain social interactions, influences how children navigate their social worlds. When sociability supports interactions, it contributes to social competence and positive social‐emotional outcomes. Although a substantial body of literature characterizes how specific parenting behaviors have an early and lasting influence on children's social development, far fewer studies have considered how characteristics of, and interactions within the parent‐child dyad influence children's sociability. For example, matching affect and behaviors during dyadic interactions may provide insight into children's openness to affiliate, and these interactions provide opportunities to model and practice responses to behavioral and emotional cues common in social interactions. One novel approach to characterizing behavioral matching in dyadic interactions is language style matching (LSM), a linguistic construct characterizing the similarity of subconscious speech patterns (i.e., function words) between members of dyads during social interaction. Although researchers have established links between LSM and other characteristics of the dyad known to influence children's social development (e.g., attachment quality), whether and how LSM predicts children's adaptive sociability among peers is currently unknown. Therefore, we examined the associations between parent‐child LSM and classroom observations of children's sociability among 151 preschoolers with elevated behavioral inhibition. Results indicated that LSM is positively associated with observed sociability in the company of classmates over and above other aspects of the parent‐child relationship (e.g., parenting). Results supported LSM as an indicator of behavioral matching and contributed to the growing body of research that considers the implications of LSM for children's social development.